Effect of empagliflozin beyond glycemic control: Cardiovascular benefit in patients with type 2 diabetes and established cardiovascular disease - Pedro Monteiro (Revista Portuguesa de Cardiologia (English Edition), 2019)
The prevalence of type 2 diabetes (T2D) continues to increase, and its association with cardiovascular (CV) disease has led to the inclusion of CV endpoints in clinical trials on the treatment of T2D.This article explores the various trials already performed and under development in this field, with particular focus on the EMPA-REG OUTCOME trial. In this trial, empagliflozin, a sodium-glucose co-transporter 2 inhibitor, demonstrated a reduction in CV risk in patients with T2D and established CV disease, in addition to CV safety and a decrease in glycated hemoglobin. This represents a paradigm shift that has led to changes in the international guidelines for the treatment of T2D. These results were maintained in subsequent subgroup analysis for heart failure, chronic kidney disease and peripheral arterial disease, although there are many questions concerning the mechanisms involved in these effects, including whether they are hemodynamic, metabolic or due to decreased myocardial cytoplasmic sodium concentrations.@page { margin: 2 cm } p { text-indent: 0.5 cm; margin-bottom: 0.21 cm; direction: ltr; color: #00000a; line-height: 120%; text-align: justify; widows: 0; orphans: 0 } p.western { font-family: ''Times New Roman'', serif; font-size: 11pt; so-language: en-US } p.cjk { font-family: ''SimSun''; font-size: 11pt; so-language: zh-CN } p.ctl { font-family: ''Mangal''; font-size: 11pt; so-language: hi-IN } a:link { so-language: zxx } With this reduction in risk for major CV events in patients with T2D, the EMPA-REG OUTCOME trial demonstrated CV protection from a hypoglycemic drug for the first time, and opened a new era in the treatment and management of T2D. This study has led to the development of ongoing trials that will establish which patients will benefit most from this therapy, particularly with regard to comorbidities. Resumo: A prevalência da diabetes mellitus tipo 2 (DMT2) continua a aumentar e a sua associação com a doença cardiovascular (CV) tem levado à incorporação e valorização de endpoints CV nos ensaios clínicos sobre o tratamento da DMT2.Este artigo faz uma revisão dos vários ensaios já realizados e em desenvolvimento, neste âmbito, com especial enfoque no estudo EMPA-REG OUTCOME. Neste estudo, a empagliflozina, um inibidor do cotransportador tipo 2 de sódio-glicose (iSGLT2), demonstrou efeitos benéficos na redução do risco CV em doentes com DMT2 e doença CV estabelecida, para além de segurança CV e diminuição dos valores de HbA1c, representando uma mudança de paradigma com impacto ao nível das recomendações internacionais para o tratamento da DMT2. Estes resultados mantiveram-se em análises de subgrupos posteriores, nomeadamente na insuficiência cardíaca, doença renal crónica e doença arterial periférica, ainda que muitas questões se coloquem sobre os mecanismos envolvidos nestes efeitos - se efeitos hemodinâmicos, efeitos metabólicos ou se a diminuição das concentrações de sódio citoplasmático no miocárdio.Com a diminuição do risco de eventos CV major em doentes com DMT2, os resultados do estudo EMPA-REG OUTCOME demonstraram, pela primeira vez, proteção CV associada ao efeito de um fármaco anti-hiperglicémico e iniciaram uma nova era no tratamento e gestão da DMT2. Este estudo levou ao desenvolvimento de outros ensaios, ainda a decorrer, que permitirão estabelecer quais os doentes que mais beneficiarão desta terapêutica, nomeadamente na relação à existência de comorbilidades. Keywords: Empagliflozin, Diabetes, Cardiovascular disease, Heart failure, PALAVRAS-CHAVE: Empagliflozina, Diabetes, Doença cardiovascular, Insuficiência cardíaca